Identification and expression profiling of flax (Linum usitatissimum L.) polyamine oxidase genes in response to stimuli - Eom, Seung Hee; Lee, Jae Kook; Kim, Dong-Ho; Kim, Heekyu; Jang, Keum-Il; Ryu, Hojin; Hyun, Tae Kyung (Acta Botanica Croatica, 2018)
Polyamine oxidases (PAOs) are known to be involved in either the terminal catabolism or the back conversion of polyamines, which affect a range of physiological processes, including growth, development, and stress responses. In this study, based on genome-wide analysis, we identified five putative PAO genes (LuPAO1 to LuPAO5) in flax (Linum usitatissimum L.) that contain the amino-oxidase domain and FAD-binding-domain. The expression analysis using quantitative real-time PCR revealed spatial variations in the expression of LuPAOs in different organs. In addition, the expression level of LuPAOs in the flax cell suspension culture was increased by treatment with methyl- jasmonate (MeJA) or pectin, but not with salicylic acid or chitosan. This indicates that LuPAOs might be involved in the MeJA-mediated biological activities. Taken together, our genome-wide analysis of PAO genes and expression profiling of these genes provide the first step toward the functional dissection of LuPAOs.